Advancements in TD-DFT: A Comprehensive Review - Amrutkar, Rakesh Devidas; Indaji, Parth Sanjay; Chaudhari, Dnyaneshwar Bhalchandra; Waghmode, Nilesh Arun; Jadhav, Mitesh Avadhut (Current Drug Research Reviews, 2025)
Time-Dependent Density Functional Theory (TDDFT) has become a key computational technique for investigating the electronic excited states of molecules. Due to its high computational efficiency, it is used for a wide range of systems, including elucidating biological structures and small molecules. The approach strikes a balance between computing cost and precision, making it a flexible tool that can be used in many different scientific fields, such as materials science, physics, and chemistry. The technique is excellent at predicting electronic absorption spectra, which makes it easier to examine the optical characteristics of molecular systems. Nevertheless, TD-DFT has limits, most notably in its ability to adequately describe some excitation types, such as tightly coupled systems and charge transfer. In order to increase accuracy, especially in situations where ordinary functionals are insufficient, the need for hybrid functionals that combine DFT and Hartree-Fock exchange is underlined. TD-DFT is nevertheless an effective method for examining the energy and characteristics of electronic excitations, despite these difficulties. When using TD-DFT, researchers should be aware of its limitations and take into account supplementary techniques to gain a thorough understanding of molecular behavior. The benefits of TD-DFT are discussed in this paper, including its effectiveness, wide range of applications, and capability to incorporate solvent effects. With further developments, TD-DFT is expected to be an essential tool for deciphering electrical structural complexities and advancing theoretical chemistry and materials science.
Keywords: DFT